2001
DOI: 10.11609/jott.zpj.16.10.604-6
|View full text |Cite
|
Sign up to set email alerts
|

A survey of gastro-intestinal parasites of captive animals at Rajkot Municipal Corporation Zoo, Rajkot, Gujarat

Abstract: A total of 28 faecal samples of different zoo mammals and seven group faecal sample of birds were examined at the Rajkot Municipal Corporation Zoo, Rajkot. Out of this, 16 (57.14%) and seven (100%) were found positive for parasitic infection in mammals and birds respectively. Among the infected mammals 11 (68.75%), three (18.75%) and three (18.75%) were positive for nematode, cestode and intestinal protozoa, respectively. In birds, nematodes and protozoans were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 1 publication
5
26
2
Order By: Relevance
“…In this the present study differs from the report of Parasani et al (2001) who revealed 68.8% animals positive for helminthic infections and 18.8% for protozoan infections in Rajkot Municipal Corporation Zoo. Both studies were conducted in a captive setting and included a variety of animal groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In this the present study differs from the report of Parasani et al (2001) who revealed 68.8% animals positive for helminthic infections and 18.8% for protozoan infections in Rajkot Municipal Corporation Zoo. Both studies were conducted in a captive setting and included a variety of animal groups.…”
Section: Discussioncontrasting
confidence: 99%
“…This is similar with the report of Parasani et al, (2001) who revealed that 50% animal's positive for helminths infection and 18.8% for protozoa in Rajkot Municipal Corporation zoo. The present study also confirms the report of Varadharajan and Kandasamy (2000) who recorded that 58% animals were positive for helminths infections and 6% were positive for protozoan infections.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is slightly higher than the report of Corden et al, (2008) who observed that the prevalence was 72.5%. On the other hand, the lower prevalence rate than the present study was recorded as 60.7% by Parasani et al, (2001), 56.3% by Lim et al, (2008), 48.1% by Modi et al,(1997), 42.4% by Reddy et al, (1992) and 40.4% by Chakraborty and Islam (1996). This may be due to geographic conditions, husbandry practice and source of feeds of the animalwhich influences the prevalence.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Ascaris sp, Toxascaris sp, Strongyloides sp, Baylisascaris sp, Ancylostoma sp, Toxacara sp and Entamoeba sp were the parasites identified in different carnivores. All the parasites recovered from the various species of carnivores were also earlier reported in Nigerian captive animals (Parsani et al, 2001;Ajibade et al, 2010;Opara et al, 2010).…”
Section: Discussionsupporting
confidence: 72%